2019
DOI: 10.1021/acsabm.9b00242
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Efficiency of Surface-Immobilized Flavobacterium-Infecting Bacteriophage

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Efforts have been made to propose methods for phage coating in medical devices [ 33 , 34 , 35 ]. For indwelling urological devices, the phage-coating is usually obtained by physical adsorption [ 33 , 36 ] and hydrogel conjugation [ 34 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made to propose methods for phage coating in medical devices [ 33 , 34 , 35 ]. For indwelling urological devices, the phage-coating is usually obtained by physical adsorption [ 33 , 36 ] and hydrogel conjugation [ 34 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tawil et al found that phages were immobilized on gold with double the density when cross-linked via L-cysteine compared to glutaraldehyde, but that no significant difference was found in the bound phages' lytic behavior 72 . Similarly, Leppänen et al rigorously compared infectivity and phage surface density after surface treatments with different combinations of 11-MUA and (3-aminopropyl)triethoxysilane (APTES), concluding that a higher phage density did not always result in a higher infectivity 95 . Indeed, Naidoo et al…”
Section: A Note On Surface Densitymentioning
confidence: 99%
“…However, differences in the orientation of phages on the feed pellets and their detachment and infectivity after the corona discharge and spray treatment, respectively, might also affect the efficiency of delivery. Leppänen et al (2019) recently showed that the antimicrobial efficiency was higher for detached phages compared to the attached ones and that covalently bound phages on carboxylate-treated gold had the lowest infectivity even if this surface was characterized by the highest number of attached phages. The authors suggest that the lost infectivity of covalently bound phages might have been caused by chemical interactions or the improper orientation of the phages on the surface ( Leppänen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“… Leppänen et al (2019) recently showed that the antimicrobial efficiency was higher for detached phages compared to the attached ones and that covalently bound phages on carboxylate-treated gold had the lowest infectivity even if this surface was characterized by the highest number of attached phages. The authors suggest that the lost infectivity of covalently bound phages might have been caused by chemical interactions or the improper orientation of the phages on the surface ( Leppänen et al, 2019 ). In our study, it does not seem that the covalently bound phages on feed pellets by the corona discharge method are characterized by a lower infectivity compared to phages applied using a spraying approach, as indicated by a very similar and stable phage number in the fish intestine when fed with the two phage-feed types.…”
Section: Discussionmentioning
confidence: 99%